2008
DOI: 10.1029/2007jc004215
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Undercurrent and North Equatorial Countercurrent at 38°W: A new perspective from direct velocity data

Abstract: [1] The western Equatorial Undercurrent (EUC) and North Equatorial Countercurrent (NECC) are investigated at 38°W using contemporaneous subsurface (ADCP) and high-resolution near-surface (drifters + satellite altimeter) velocity measurements, together with hydrographic (CTDO 2 ) data that were collected from 1998 to 2006. The observations reveal an EUC with a strong semiannual pattern of intensification. Direct measurements also confirm the existence of a northern branch of the NECC (nNECC), observed here for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 41 publications
(82 reference statements)
3
34
0
Order By: Relevance
“…They found a strong exchange between the nNECC and the NECC/NEUC. The northern core of the NECC was noted by Urbano et al [2008] as well between 9° and 15°N farther west, during measurements at the PIRATA mooring position at 38°W. They found a meandering NECC and two cores developing when the ITCZ reaches its northernmost location.…”
Section: Discussionmentioning
confidence: 92%
“…They found a strong exchange between the nNECC and the NECC/NEUC. The northern core of the NECC was noted by Urbano et al [2008] as well between 9° and 15°N farther west, during measurements at the PIRATA mooring position at 38°W. They found a meandering NECC and two cores developing when the ITCZ reaches its northernmost location.…”
Section: Discussionmentioning
confidence: 92%
“…The time-mean eastward surface velocity at 5 N between 40 and 20 W is approximately 0.2-0.25 mÁs 21 [Lumpkin and Garzoli, 2005]. But the eastward velocity of the NECC is stronger during early summer and exhibits strong interannual variation, for example, with a value of about 0.2 mÁs 21 in July 2004 and 0.4 mÁs 21 in July 2005 [Urbano et al, 2008]. The eastward propagation speed estimated from the Aquarius data in the second half of 2012 using Radon Transform is 0.81 mÁs 21 for the unfiltered data and 0.53 mÁs 21 for the 4-20 , 20-50 day band-pass filtered data.…”
Section: Spatial and Temporal Signature Of Tiws In Sss Sst And Sshmentioning
confidence: 99%
“…Johns et al (2014) have recently shown that this is the case in the central Atlantic but not so in the eastern basin. Velocity measurements at moorings also suggest substantial seasonal changes in vertical structure, as the EUC shallows/deepens during the boreal spring/fall (Brandt et al, 2006;Urbano et al, 2008;Johns et al, 2014). Hüttl-Kabus and Böning (2008), using a high-resolution numerical model, found the NEUC to transport between 4 Sv and 7 Sv at 35°W (a predominant annual cycle) and the SEUC to range between 1.2 Sv and 4.5 Sv at 23°W (semiannual cycle).…”
Section: Seasonal Tropical Variabilitymentioning
confidence: 95%
“…The spatial structure of the mean surface tropical currents is characterized by zonal jets that alternate in latitude (Stramma and Schott, 1999;Schott et al, 2003Schott et al, , 2004Lumpkin and Garzoli, 2005;Hüttl-Kabus and Böning, 2008;Urbano et al, 2008;RosellFieschi et al, 2015). The predominant flow is the westward South Equatorial Current (SEC) but close to the Equator we find the eastward Equatorial Undercurrent (EUC) along 0°, flanked by its northern and southern branches (NEUC and SEUC) at latitudes between 3°and 4°.…”
Section: Mean Equatorial Surface Fieldsmentioning
confidence: 96%
See 1 more Smart Citation